Inhomogeneous relativistic plasma dielectric tensor - Pavlov, S.S. (Вопросы атомной науки и техники, 2011)
The paper is concerned with the method to derive the inhomogeneous relativistic plasma dielectric tensor on the base principle of analytic continuation for Cauchy-type integrals and the exact plasma dispersion functions concept.